Self-care behavior and associated factors among patients with heart failure in public hospitals of Southeast Ethiopia. Issue 8 (August 2022) - Getachew, Almaz; Assefa, Tesfaye; Negash, Wogene
Objective: This study was performed to assess self-care behavior and associated factors among patients with heart failure attending public hospitals in Southeast Ethiopia in 2021. Methods: An institutional-based cross-sectional study was conducted among 420 patients with heart failure from 15 May to 30 June 2021 using a simple random sampling technique. A multivariable binary logistic model was used to identify factors associated with self-care behavior. Statistical significance was declared at p < 0.05. Results: The magnitude of good self-care behavior among patients with heart failure was 53.6% [95% confidence interval (CI), 48.9–58.3]. Factors associated with self-care behavior were treatment with a beta blocker [adjusted odds ratio (AOR), 0.49; 95% CI, 0.27–0.89], treatment with digitalis (AOR, 0.11; 95% CI, 0.05–0.24), the level of social support (AOR, 0.07; 95% CI, 0.03–0.15), and the presence of depressive symptoms (AOR, 0.21; 95% CI, 2.70–8.33). Conclusion: Slightly more than half of the respondents had good self-care behavior. Attention should be given to enhancing good self-care practice through integration of health education as routine care.